2010
DOI: 10.15517/rbt.v0i0.3391
|View full text |Cite
|
Sign up to set email alerts
|

Trophic levels of fish species of commercial importance in the Colombian Caribbean

Abstract: Ecological studies on commercial important fish species are of great value to support resource management issues. This study calculated trophic levels of those Colombian Caribbean fish species whose diet has been locally described. Usable diet data of 119 species resulted in 164 trophic level estimates. An ordinary regression model relating trophic level and fish size was formulated. The regression slope was positive and significantly different from zero (p<0.05) suggesting a scaling of trophic level with fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
3
6
0
Order By: Relevance
“…In addition to the general description of the trophic levels, we found that the trophic level had a positive increase with body size (Pauly, Trites, Capuli, & Christensen, ). Similar to previous studies conducted in the Mediterranean Sea (Stergiou & Karpouzi, ) and the Colombian Caribbean (García & Contreras, ), the trophic level showed a positive correlation with body length. Because of the different types of feeding habits, most fishes feed on a variety of trophic levels, leading to a close relationship between the food chains.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to the general description of the trophic levels, we found that the trophic level had a positive increase with body size (Pauly, Trites, Capuli, & Christensen, ). Similar to previous studies conducted in the Mediterranean Sea (Stergiou & Karpouzi, ) and the Colombian Caribbean (García & Contreras, ), the trophic level showed a positive correlation with body length. Because of the different types of feeding habits, most fishes feed on a variety of trophic levels, leading to a close relationship between the food chains.…”
Section: Discussionsupporting
confidence: 89%
“…Two rhinobatids [ R. productus and Rhinobatos percellens ] had T L values ranging between 3·6 and 3·7 according to stomach content data (F. Valenzuela‐Quiñonez, unpubl. data; Bornatowski et al, ; García & Contreras, ). Other studies reported T L values of 3·6–4·2, using stable‐isotope analysis (F. Valenzuela‐Quiñonez, unpubl.…”
Section: Discussionmentioning
confidence: 93%
“…There are very few estimates of the trophic level of guitarfishes, especially in the Mexican Pacific and GC, because these species do not have great commercial importance. This study calculated the trophic level using stomach content data, which is widely used for elasmobranchs in general (Cortés, , ; Ebert & Bizarro, ; Navia et al, ; García & Contreras, ; López‐García et al, ; Bornatowski et al, 2014 a , b ), resulting in T L values of c . 3·6.…”
Section: Discussionmentioning
confidence: 99%
“…The weighted average of the trophic level (Rochet and Trenkel 2003) of landings was used as a functional indicator to measure the impact of the artisanal set gill net fishery on demersal fish assemblages. The trophic level of each taxon was obtained from data reported by García and Contreras (2011) and the Fishbase dataset (Froese and Pauly 2017).…”
Section: Determination Of Functional and Fisheries Indicatorsmentioning
confidence: 99%